2017
DOI: 10.1111/jace.15385
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesis mechanism of 15R–SiAlON reinforced Al2O3 refractories by Fe–Si liquid phase sintering

Abstract: 15R-SiAlON bonded Al 2 O 3 refractories were successfully synthesized using ferrosilicon nitride and alumina by liquid phase sintering. The phase composition and morphology were analyzed by means of X-ray diffraction, scanning electron microscopy, and transmission electron microscopy. The results show that 15R-SiAlON reinforcement can be in situ obtained in the specimens with 5 wt% ferrosilicon nitride at 1500°C to 1700°C in flowing N 2 of 0.1 MPa. The morphology of 15R-SiAlON is strongly dependent on the morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…It was also reported that transition metal oxides including NiO and Fe 2 O 3 not only helped reduce the temperature of mullite formation, but had an important influence on the morphology of mullite rods and then enhanced the strength of Al 2 O 3 ‐C refractories 37 . Therefore, one‐dimensional ceramic reinforcement phases in the matrix, such as in situ formed SiC whiskers, MWCNTs, and mullite rods, can effectively enhance the mechanical properties of Al 2 O 3 ‐C refractories 38–40 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also reported that transition metal oxides including NiO and Fe 2 O 3 not only helped reduce the temperature of mullite formation, but had an important influence on the morphology of mullite rods and then enhanced the strength of Al 2 O 3 ‐C refractories 37 . Therefore, one‐dimensional ceramic reinforcement phases in the matrix, such as in situ formed SiC whiskers, MWCNTs, and mullite rods, can effectively enhance the mechanical properties of Al 2 O 3 ‐C refractories 38–40 …”
Section: Introductionmentioning
confidence: 99%
“…37 Therefore, one-dimensional ceramic reinforcement phases in the matrix, such as in situ formed SiC whiskers, MWCNTs, and mullite rods, can effectively enhance the mechanical properties of Al 2 O 3 -C refractories. [38][39][40] At the same time, we investigated intensively a novel strategy to enhance the mechanical properties of refractories by using microporous aggregates with a large number of micropores. [41][42][43][44][45] The microporous corundum aggregates were prepared by in situ decomposition synthesis, 46 which utilizes the decomposition of raw materials to form pores.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Recently, the application of non-oxide composite refractories has been increasingly tapped into in high-temperature industry, among which AlN-AlON composites are considered to be a composite refractory owing to their excellent high temperature strength, thermal shock resistance, oxidation resistance, and good corrosion resistance to metallurgical slag and alkali. [11][12][13][14] To fabricate AlN-AlON composites, complex raw materials of Al, AlN, Al 2 O 3, and C were commonly prepared respectively prior to the mechanical mixing. [15][16][17] Although it is simple and readily regulates the constituent of the raw-material powders, the chemical compositions tend to exhibit inhomogeneous locally in the final composites due to the challenge in thorough mixing, and the mixing degree of various raw-material powders is also restricted by the grain size.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of modern steel metallurgy technology, continuous deepening of energy saving, emission reduction, and manufacture efficiency improvement, the clean steel technology requires an extremely low carbon content in the steel 7–10 . Recently, the application of non‐oxide composite refractories has been increasingly tapped into in high‐temperature industry, among which AlN–AlON composites are considered to be a composite refractory owing to their excellent high temperature strength, thermal shock resistance, oxidation resistance, and good corrosion resistance to metallurgical slag and alkali 11–14 …”
Section: Introductionmentioning
confidence: 99%
“…Kaolinite, 36 natural clay containing kaolin, and quartz 37 were chosen as low cost ingredients to synthesize β‐Sialon. And in most of relative reports, SiO 2 , Si 3 N 4 , and Al 2 O 3 38‐43 are commonly used as starting materials to produce composites containing Sialon. Therefore, Al 2 O 3 and SiO 2 in BAS provide a theoretical possibility to in situ synthesize Sialon in the BAS by one‐step method.…”
Section: Introductionmentioning
confidence: 99%